2019
DOI: 10.1088/1748-9326/ab2dcb
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of multiple PM2.5 exposure products for estimating health benefits of emission controls over New York State, USA

Abstract: Ambient exposure to fine particulate matter (PM 2.5 ) is one of the top global health concerns. We estimate the PM 2.5 -related health benefits of emission reduction over New York State (NYS) from 2002 to 2012 using seven publicly available PM 2.5 products that include information from groundbased observations, remote sensing and chemical transport models. While these PM 2.5 products differ in spatial patterns, they show consistent decreases in PM 2.5 by 28%-37% from 2002 to 2012. We evaluate these products u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 85 publications
(73 reference statements)
1
30
0
Order By: Relevance
“…The Dalhousie V4.NA.02 data for 2011 shown in Figure 1c capture the spatial gradients of the county-level monitoring data in Figure 1d. The Dalhousie data seem to show the best agreement with the AQS+IMPROVE data in the remote areas of the western U.S. and New England, which is consistent with another comparison study (Jin et al, 2019b). This feature indicates that incorporating satellite data can be valuable for improving estimation of PM 2.5 concentrations in remote areas where monitor coverage is sparse.…”
Section: Major Pm 25 Exposure Datasetssupporting
confidence: 86%
See 1 more Smart Citation
“…The Dalhousie V4.NA.02 data for 2011 shown in Figure 1c capture the spatial gradients of the county-level monitoring data in Figure 1d. The Dalhousie data seem to show the best agreement with the AQS+IMPROVE data in the remote areas of the western U.S. and New England, which is consistent with another comparison study (Jin et al, 2019b). This feature indicates that incorporating satellite data can be valuable for improving estimation of PM 2.5 concentrations in remote areas where monitor coverage is sparse.…”
Section: Major Pm 25 Exposure Datasetssupporting
confidence: 86%
“…Because ground-based monitors, satellites, and models are often combined to estimated surface PM 2.5 , there are few independent data sources for validation. A recent study over New York State uses independent ground-based observations from the New York City Community Air Quality Survey (NYCCAS) Program and the Saint Regis Mohawk Tribe Air Quality Program to evaluate seven PM 2.5 products (Jin et al, 2019b). Jin et al suggest inclusion of satellite remote sensing improves the estimate of surface PM 2.5 in the remote area, but little gains over urban area.…”
Section: Ongoing and Future Research Effortsmentioning
confidence: 99%
“…2015 ; Wu et al. 2019 ) given that the model we used has been shown to perform well even at rural locations in NYS ( Jin et al. 2019 ) and, thus, any error is likely nondifferential.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prediction model has excellent predictive accuracy (van Donkelaar et al 2019) and is highly spatially resolved to capture population-averaged county-level exposures, some exposure measurement error is still expected. Any resulting bias, however, is expected to be toward the null (Kioumourtzoglou et al 2014;Hart et al 2015;Wu et al 2019) given that the model we used has been shown to perform well even at rural locations in NYS (Jin et al 2019) and, thus, any error is likely nondifferential. First hospitalization data are likely to miss a number of cases because patients may not be hospitalized even as disease symptoms worsen.…”
Section: Limitationsmentioning
confidence: 99%
“…All PM 2.5 datasets used in this study provided daily PM 2.5 concentrations. More details regarding the PM 2.5 products, including validation and comparative statistics, can be found in an existing publication [ 25 ].…”
Section: Methodsmentioning
confidence: 99%